2018
DOI: 10.3758/s13415-018-00666-z
|View full text |Cite
|
Sign up to set email alerts
|

Contingency awareness as a prerequisite for differential contextual fear conditioning

Abstract: Contingency awareness during conditioning describes the phenomenon of becoming consciously aware of the association between a conditioned stimulus (CS) and an unconditioned stimulus (US). Despite the fact that contingency awareness is necessary for associative learning in some conditioning paradigms, its role in contextual fear conditioning, a variant that uses a context-CS (CTX) instead of a cue, has not been characterized thus far. We investigated if contingency awareness is a prerequisite for contextual fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 79 publications
2
19
0
Order By: Relevance
“…We find the low level of contingency knowledge and its impact on conditioning measures interesting (as it highlights the role of the observer's attention and the observational stimulus quality), but not surprising, given that the role of contingency knowledge has been described for various conditioning protocols and conditioning measures, e.g. 31,42,43 . Skin conductance response has been reported as a measure reflecting contingency learning 44 , while potentiation of the acoustic startle reflex has been claimed to be more valence-specific and less dependent on attention 45 , although see 46 , but its relation to contingency awareness is still unclear.…”
Section: Discussionmentioning
confidence: 60%
“…We find the low level of contingency knowledge and its impact on conditioning measures interesting (as it highlights the role of the observer's attention and the observational stimulus quality), but not surprising, given that the role of contingency knowledge has been described for various conditioning protocols and conditioning measures, e.g. 31,42,43 . Skin conductance response has been reported as a measure reflecting contingency learning 44 , while potentiation of the acoustic startle reflex has been claimed to be more valence-specific and less dependent on attention 45 , although see 46 , but its relation to contingency awareness is still unclear.…”
Section: Discussionmentioning
confidence: 60%
“…The ambiguity, however, should have been reduced by the fact that the observers were familiar with the demonstrators and thus more likely to be sensitive to their We find the low level of contingency knowledge and its impact on conditioning measures interesting (as it highlights the role of the observer's attention and the observational stimulus quality), but not surprising, given that the role of contingency knowledge has been described for various conditioning protocols and conditioning measures (e.g. Baeuchl et al, 2019;Tabbert et al, 2006Tabbert et al, , 2011Weidemann et al, 2016). While skin conductance response has been reported as a measure reflecting contingency learning (Sevenster et al, 2014), a potentiation of the acoustic startle reflex has been claimed to be a specific index of fear acquisition, not requiring contingency awareness (Hamm & Vaitl, 1996;Hamm & Weike, 2005) and generally considered to be more valence-specific and less dependent on attention (Lang et al, 1990; although see Mertens & De Houwer, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…The general consensus is that associative learning depends on contingency awareness (CA) (Baeuchl et al, 2019;Mertens & Engelhard, 2020;Weidemann et al, 2016). This is not supported by the current study: Not only did none of the participants in the Reducedvisibility groups demonstrate CA, most failed to even recall any prime.…”
Section: Discussionmentioning
confidence: 99%
“…Even for visible stimuli, the role of contingency awareness (CA; the awareness of US-CS relationship) is still being debated. The requirement of CA appears to be procedure-dependent, but in general CA is required for successful conditioning (Baeuchl, Hoppstädter, Meyer, & Flor, 2019;Mertens & Engelhard, 2020;Weidemann, Satkunarajah, & Lovibond, 2016). In a comprehensive study using word stimuli as US, Greenwald and De Houwer (2017) suggested that different processes are involved in conditioning involving visible versus subliminal stimuli: The former requires contingency awareness, but the later does not.…”
Section: Semantic Processing Of Subliminal Wordsmentioning
confidence: 99%